Multimedia Pembelajaran Kimia Pada Sekolah Menengah Atas (SMA) PGRI Kota Pagar Alam - Nanda prawira (BETRIK, 2025)
Chemistry learning at the high school level often presents unique challenges. The subject matter is inherently abstract and difficult to grasp, while limited teaching aids and minimal use of technology further contribute to low student motivation and achievement. Observations at SMA PGRI Kota Pagar Alam revealed that although 85% of students own smartphones, these devices have yet to be fully utilized to support learning.This study focuses on developing an interactive chemistry learning multimedia application using the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The final product integrates animations, simulations, gamebased interactive quizzes, and audio narration into a cohesive learning experience.Expert validation from the fields of media, content, language, and design yielded an average score above 4.5—classified as highly feasible—with visual quality (4.70) and content relevance (4.65) standing out as key strengths. Testing with 30 eleventh-grade students showed a substantial improvement in understanding, with the average score increasing from 58.2 (pretest) to 82.4 (posttest), representing a 41.6% gain. Furthermore, 87% of students reported that the multimedia helped them better comprehend chemistry concepts, while 92% found the interface engaging and interactive.These findings affirm that combining visual, audio, and interactive elements can significantly enhance the effectiveness of chemistry learning. Looking ahead, this multimedia application holds strong potential for broader implementation, including personalized learning content and the incorporation of game elements to create a more immersive experience. With adequate teacher training and proper device availability, this innovation could serve as a sustainable solution to address the challenges of chemistry education in schools.